2016
DOI: 10.1007/s00246-016-1407-6
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Resident Attitudes and Knowledge of Critical Congenital Heart Disease Screening

Abstract: This study aimed to understand the knowledge, attitudes and confidence level related to critical congenital heart disease (CCHD) screening among pediatric residents. Pediatric residents were assessed via an anonymous survey related to CCHD guidelines and procedures as set out by the New York State Department of Health. The survey was emailed to pediatric residents at a large academic institution. A teaching intervention was performed after the initial survey, which was followed by an identical after-interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Some form of inclusion of the same in curriculum could increase knowledge about proper documentation and improve confidence among medical providers when they start with actual patient practice as trainee physicians. 8 If the provider is comfortable with the same, the efficiency of documentation will likely increase and this might reflect into reduced documentation times.…”
Section: Discussionmentioning
confidence: 99%
“…Some form of inclusion of the same in curriculum could increase knowledge about proper documentation and improve confidence among medical providers when they start with actual patient practice as trainee physicians. 8 If the provider is comfortable with the same, the efficiency of documentation will likely increase and this might reflect into reduced documentation times.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 4% of the questions on the American Board of Pediatrics (ABP) General Pediatrics certification exam are related to cardiology [2]. Unfortunately, one pediatric residency program reported only 38% confidence with a fundamental topic like critical CHD screening [3]. Pediatric cardiologists and pediatric residency program directors need to ensure that all general pediatric residents receive adequate training in this area.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that 75% of neonates with missed CCHD diagnoses had a form of aortic obstruction [ 10 ]. Though the implementation of CCHD screening was initiated in 2011, many physicians who work outside of neonatology are unfamiliar with the screening process and are unaware about which diagnoses can be missed through this screening process [ 11 ].…”
Section: Discussionmentioning
confidence: 99%